Social Capital and Entrepreneurial Orientation on Micro-business Performance: A Study on Business Actors in East Nusa Tenggara - Marianus Hendrilensio Sanga (Journal of Business, Accounting and Information Technology, 2026)
Micro-enterprises play a crucial role in regional economic development, particularly in employment creation and poverty reduction. However, their performance in less-developed regions remains constrained by limited resources and structural challenges. This study examines the effects of social capital and entrepreneurial orientation on micro-enterprise performance in East Nusa Tenggara, Indonesia. Using a quantitative explanatory approach, data were collected through a survey of 50 micro-entrepreneurs in Kupang City and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that both social capital and entrepreneurial orientation have positive and significant effects on micro-enterprise performance. Entrepreneurial orientation reflected in innovativeness, proactiveness, and risk-taking, exhibits a stronger influence than social capital. Furthermore, the two variables jointly explain 58.7% of the variance in micro-enterprise performance, indicating substantial explanatory power. These findings highlight that non-financial factors play a vital role in enhancing micro-enterprise performance, particularly in regions characterized by strong social ties but limited institutional support. This study contributes to the entrepreneurship literature by integrating social capital and entrepreneurial orientation within a single empirical model and offers practical implications for micro-enterprise development policies that emphasize not only financial assistance but also the strengthening of social networks and entrepreneurial capabilities.